Apresiasi Keimanan kepada Tuhan melalui Pengalaman Spiritual - Kadir, Abdul (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2015)
The awareness of God departed from religion which becomes introverted understanding in one?s experience. Appreciation of God should not be limited to the value of formalities by simply doing spirituality teaching, but also the embodiment of spiritual experience of God. The constellation of religious values is not just about understanding and appreciation but also achieve esoteric experience, so as to reveal its meaning for deeper appreciation, recognition and encounter with Him. Esoteric aspect of religion has become an important goal in the appreciation of spiritual experience ascent and acquisition with cleaning bonds which related to plurality and turned it from horizontal dimension senses to the vertical dimension of the universe to reach the consciousness of mortality. If God wills, there will be an incline in spiritual sensing sharpness until one can see, watch, or feel the real evidence from God about the things that are obviously high, so that the faith based on mukâshafah, ma?rifah, and mushâhadah namely faith through spiritual vision to arrive at the essence.